Review paperChemokines in pathogenesis of bullous diseases - Erkiert-Polguj, Anna; Żebrowska, Agnieszka; Dziankowska-Bartkowiak, Bożena; Waszczykowska, Elżbieta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Chemokines are small proteins produced by leukocytes, keratinocytes, fibroblasts and endothelial cells. This group of cytokines attracts leukocytes to the site of inflammation, thus taking part in the immune response. Recent research has revealed their role in angiogenesis, embriogenesis, organogenesis and in pathogenesis of many diseases. In this article current data about chemokines’ structure and function and also their role in bullous skin disease pathogenesis have been discussed.